Patients perceptions of virtual reality therapy in the management of chronic cancer pain - Bernard M. Garrett; Gordon Tao; Tarnia Taverner; Elliott Cordingley; Crystal Sun (Heliyon, 2020)
The management of chronic cancer pain remains challenging and complex, with the process often involving a variety of pharmacological and non-pharmacological approaches. Recent studies have shown virtual reality (VR) therapy to be successful in the management of acute pain. However, it remains unclear whether VR-based applications are effective as an adjunctive therapy for cancer patients with chronic pain. Moreover, there exists a gap in the current research landscape that address patient's perceptions of virtual reality therapy. This qualitative study enrolled patients from a larger ongoing randomized controlled clinical trial in two focus groups covering topics including patients experience with and perspectives on using VR for chronic pain control, both generally, and specific to their own circumstances. Five major thematic categories and 23 sub-categories emerged in the analysis process reflecting the participants' narrative. Similar to other research, this study found mixed results in the use of adjunctive VR therapy to manage chronic cancer pain, although a majority of respondents found it to be beneficial. This study confirms that pain management is a highly complex and individualized process. For maximum efficacy, it is recommended that future designs of VR interventions engage pain patients in the design process to ensure maximum efficacy of experiences to with individuals' preferences.